Characterizing and Defining of Designing Sustainable Product-Service Systems Applied to Distributed Water-Energy-Food Nexus - Gao, Meng; He, Renke; Vezzoli, Carlo; Ma, Ke; Zhang, Yuting (Frontiers in Environmental Science, 2022)
The Water-Energy-Food (WEF) Nexus address significantly and effectively sustainability issue internationally. However, there has been little attention paid to the WEF Nexus challenges related to sustainable livelihoods, such as resource access, resource security, and resource utilization. Given the need to establish design research, policy formulation, and resource management based on end-user needs, new research hypotheses and available models must be proposed on a small-scale scale of households and communities. This paper combines the Sustainable Product-Service System (SPSS) and Distributed Economies (DE), two prospective and intertwined models combining environmental, social, and economic sustainability with the WEF Nexus approach, to emphasize the shifting to small-scale and highly localized WEF systems the product and service system based on the satisfaction unit, i.e., designing SPSS applied to Distributed WEF Nexus. This paradigm shift is presented and detailed in an eleven dimensions canvas with the analytical, conceptual research approach, helps to define and analyze the characteristics of existing solutions and promote innovative ideas or scenarios in sustainable WEF nexus. The new 11-dimensional canvas tool, in particular, is thought to have the potential to become a basic research analysis and innovative strategic tool in this field after being tested and evaluated by forty companies, experts, and designers in China and Italy. Finally, despite considerable implementation obstacles, this innovative application of multi-mode integration still has the potential for win-win sustainability, to meet human needs for clean water, safe energy, and sufficient food, ultimately accelerating the transition to a sustainable society.